The effects of the structural stiffness of vibration transfer path on friction-induced vibration and noise. (September 2022) - Liu, Q.A.; Xiang, Z.Y.; Mo, J.L.; Zhang, Q.X.; Zhu, Y.G.
Abstract: Experimental and numerical analysis was conducted to study the effect of structural stiffness of transfer path on friction-induced vibration and noise (FIVN), by replacing fixture devices with different structural stiffnesses. The results show that the low-stiffness system and high-stiffness system are prone to generate strong FIVN, while the system with moderate structural stiffness exhibits a better FIVN performance. This is due to, indicated by the interfacial tribology analysis, that the moderate structural stiffness can leads to mild surface wear at the contact interface. Therefore, to better understand evolution of the interfacial tribological behavior and research the generation mechanism of FIVN, it is necessary to develop a test device avoiding the influence of structural stiffness on the test results. Graphical Abstract: ga1 Highlights: Effect of the structural stiffness on interfacial tribological behavior was studied. Impact of contact inclination angle on contact stress distribution was explained. Dynamic correlations of contact behaviors were discussed. Relationships between structural stiffness and FIVN of system were explored.